Laparoscopic Ischemic Conditioning of the Stomach for Esophageal Replacement - Hölscher, Arnulf H. (2007)
OBJECTIVES: A considerable percentage of morbidity and mortality after esophagectomy and gastric pull-up is due to leakage of the esophagogastrostomy, which is mainly caused by ischemia of the gastric fundus. Previous clinical studies demonstrated that impaired microcirculation of the gastric conduit almost recovers within the first 5 postoperative days. Therefore, this study was designed to improve gastric perfusion by laparoscopic ischemic conditioning of the stomach. METHODS: The study group consisted of 83 patients with 44 esophageal adenocarcinomas and 39 squamous cell carcinomas. A total of 51% received neoadjuvant radiochemotherapy. First, all patients underwent laparoscopic mobilization of the stomach including the cardia and preparation of the gastric conduit. After a mean delay of 4.3 days (range, 3–7 days), a conventional right-sided transthoracic en bloc esophagectomy was performed. Reconstruction was done by gastric pull-up and high intrathoracic esophagogastrostomy. RESULTS: Three conversions (3.6%) to open surgery were necessary during laparoscopic mobilization of the stomach. The reoperation rate was 2.4% (one relaparoscopy for control of a bleeding of the stapler line, one rethoracotomy for chylothorax). Two patients showed circumscribed necroses of the upper part of the fundus after gastric pull-up into the chest. These necroses were resected for reconstruction by esophagogastrostomy. Five patients (6.0%) developed small anastomotic leakages with minor clinical symptoms; however, the gastric conduits were well vascularized. All leakages healed after endoscopic stenting. Major postoperative complications were observed in 13.3% of the patients and the 90-day mortality was 0%. CONCLUSION: Laparoscopic ischemic conditioning of the gastric conduit is feasible and safe and may contribute to the reduction of postoperative morbidity and mortality after esophagectomy and gastric pull-up.